Moving Statues and Moving Images: Religious Artefacts and the Spiritualisation of Materiality - Eipper, Chris (The Australian journal of anthropology, 2007)
This paper addresses the spiritualisation of materiality integral to the expression of religious experience by devotees. It focuses on the ‘objective correlatives' of emotion-imbued faith. Although primarily concerned with the aesthetics of contemporary Catholic mysticism, the aim is to suggestively allude to the implications for comparative analysis. Beginning with devotion to the rosary, it addresses the ‘moving statues' phenomenon, which in the mid-1980s in Ireland led to numerous visionaries experiencing apparitions of the Virgin Mary. Arguing that sensory analogues are indispensable to the expression of feelings and thoughts, it directs our attention to the tensions implicit in the process, i.e., to the way humans (in this case, religious devotees) need to find and fix upon an adequate and appropriate sensory equivalent. It stresses that such tensions are integral to the formulation and communication of meaning. Further consideration of the imaginative power of material representations leads into a discussion of the influence now exerted by the moving image. The depiction of penitential suffering in The Passion of the Christ is then used to illustrate how film can function as an objective correlative, in this case by articulating notions of penance and redemption shared by Irish visionaries and their disciples.